A STUDY ON RECRUITMENT AND SELECTION PRACTICES - A THEORETICAL APPROACH - Saroj Bandi, Ganga Naga; Kumar, Dr. G.Praveen (IJRDO - Journal of Business Management, 2017)
Recruitment and selection are two important phases in Human resource Management. This Article mainly Outline theoretical concepts like Recruitment sources, Factors effecting Recruitment, selection and selection methods. Still some people assume that both recruitment and selection are identical and same. But there is a lot of difference exists between them. Recruitment is a positive process that attracting more applicants, while selection is a negative process of picking the right persons at right places according to the selection criteria. This article also put forth effort on contemporary issues in recruitment and selection.